2022
DOI: 10.3389/fimmu.2022.956181
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory roles of selenium nanoparticles: Novel arts for potential immunotherapy strategy development

Abstract: Current chemotherapy strategies used in clinic appear with lots of disadvantages due to the low targeting effects of drugs and strong side effects, which significantly restricts the drug potency, causes multiple dysfunctions in the body, and even drives the emergence of diseases. Immunotherapy has been proved to boost the body’s innate and adaptive defenses for more effective disease control and treatment. As a trace element, selenium plays vital roles in human health by regulating the antioxidant defense, enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 141 publications
1
17
0
1
Order By: Relevance
“…The results meant that BRP-SeNPs possessed high Zeta potential had low aggregation and high stability. However, some studies reported that with the increasing of concentration of polysaccharide, the particle size of synthetic polysaccharide-SeNPs would get smaller ( Chen et al, 2022 ). We speculated that the strong molecular interaction between polysaccharides was likely to lead to the weakened binding ability of BRP to SeNPs in our research.…”
Section: Resultsmentioning
confidence: 99%
“…The results meant that BRP-SeNPs possessed high Zeta potential had low aggregation and high stability. However, some studies reported that with the increasing of concentration of polysaccharide, the particle size of synthetic polysaccharide-SeNPs would get smaller ( Chen et al, 2022 ). We speculated that the strong molecular interaction between polysaccharides was likely to lead to the weakened binding ability of BRP to SeNPs in our research.…”
Section: Resultsmentioning
confidence: 99%
“…Selenium (Se) NPs are characterized by low toxicity and high degradability, and immunomodulatory capability by targeting macrophages and regulating their polarization [ 191 ]. In drug delivery, Se NPs can be conjugated with high concentrations of various types of agents, which enhances their concentration at the targeted site of delivery.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…14 SeNPs play an immune role in coordination with other cells. A , C SeNPs and NPs enhance the activity of other cells to promote an antitumor effect [ 285 , 286 ]. Copyright 2022, Chen, Yang, Fan, Jin, Liao, Li, Liu, Liang, Zhang, Xu and Pi.…”
Section: Tumor Immunotherapy Based On Senpsmentioning
confidence: 99%